Serum caspase-9 levels are increased in patients with amyotrophic lateral sclerosis - Iłżecka, Joanna (Springer Milan, 2011)
It is known that apoptosis may play a role in the pathophysiology of amyotrophic lateral sclerosis (ALS). Moreover, caspase-9 is implicated in the apoptosis pathway. The aim of the study was to investigate caspase-9 levels in serum of patients with ALS. The study involved 30 patients with ALS and 30 patients from the control group. The serum caspase-9 levels were measured using the enzyme-linked immunosorbent method. The study showed that caspase-9 levels are significantly increased in serum of the patients with ALS comparing to the control group (p < 0.05). There was a significant correlation of serum caspase-9 levels with severity of clinical state of ALS patients and duration of the disease (p < 0.05). The results indicate that caspase-9 may be implicated in pathomechanism of neurodegeneration in ALS.